2015
DOI: 10.1007/s13760-015-0465-5
|View full text |Cite
|
Sign up to set email alerts
|

Mirror therapy enhances upper extremity motor recovery in stroke patients

Abstract: The purpose of this study was to evaluate the effects of mirror therapy program in addition with physical therapy methods on upper limb recovery in patients with subacute ischemic stroke. 15 subjects followed a comprehensive rehabilitative treatment, 8 subjects received only control therapy (CT) and 7 subjects received mirror therapy (MT) for 30 min every day, five times a week, for 6 weeks in addition to the conventional therapy. Brunnstrom stages, Fugl-Meyer Assessment (upper extremity), the Ashworth Scale, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 31 publications
4
19
0
1
Order By: Relevance
“…Eight studies reported intergroup differences after the intervention, with values of Cohen's d as follows: 1.70 (Park et al ., ), 1.12 (Samuelkamaleshkumar et al ., ), 1.00 1.35 (Kim et al ., ), 0.98 (Arya et al ., ), 0.76 (Kojima et al ., ), 0.58–0.76 (Lee, Cho et al ., ), 0.49 (Michielsen et al ., ), 0.37 (Wu et al ., ) and 0.28–0.38 (Lin et al ., ). In addition, in five studies there was a post‐intervention improvement in function in the intervention group, with values of Cohen's d as follows: 1.55 (Mirela Cristina et al ., ), 1.15 (Samuelkamaleshkumar et al .), 1.15–1.87 (Lee, Cho et al ., 2012), 1.00–1.35 (Kim et al ., ) and 0.19–0.72 (Lee, Lee et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight studies reported intergroup differences after the intervention, with values of Cohen's d as follows: 1.70 (Park et al ., ), 1.12 (Samuelkamaleshkumar et al ., ), 1.00 1.35 (Kim et al ., ), 0.98 (Arya et al ., ), 0.76 (Kojima et al ., ), 0.58–0.76 (Lee, Cho et al ., ), 0.49 (Michielsen et al ., ), 0.37 (Wu et al ., ) and 0.28–0.38 (Lin et al ., ). In addition, in five studies there was a post‐intervention improvement in function in the intervention group, with values of Cohen's d as follows: 1.55 (Mirela Cristina et al ., ), 1.15 (Samuelkamaleshkumar et al .), 1.15–1.87 (Lee, Cho et al ., 2012), 1.00–1.35 (Kim et al ., ) and 0.19–0.72 (Lee, Lee et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Motor recovery of hemiplegic arms and hands was analysed in five studies (Arya et al ., ; Kim et al ., ; Lee, Cho et al ., 2012; Mirela Cristina et al ., ; Samuelkamaleshkumar et al ., ). Four studies reported a post‐intervention improvement in motor performance in the MT group (Kim et al ., ; Lee, Cho et al ., 2012; Mirela Cristina et al ., ; Samuelkamaleshkumar et al .), values of Cohen's d ranged between 1.27 and 1.38 (Kim et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations